2012
DOI: 10.1264/jsme2.me11325
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Anaerobic Bacteria for Symbiotic Recycling of Uric Acid Nitrogen in the Gut of Various Termites

Abstract: Recycling of the nitrogenous waste uric acid (UA) of wood-feeding termites by their gut bacteria is one of the significant aspects of symbiosis for the conservation of nitrogen sources. Diverse anaerobic UA-degrading bacteria comprising 16 species were isolated from the gut of eight termite species, and were assigned to Clostridia, Enterobacteriaceae, and low G+C Gram-positive cocci. UA-degrading Clostridia had never been isolated from termite guts. UA-degrading ability was sporadically distributed among phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 61 publications
(80 reference statements)
3
73
0
1
Order By: Relevance
“…These 44 OTUs were assigned to 24 genera. We found that 12 of the 24 genera had been previously observed (Butera, Ferraro, Alonzo, Colazza, & Quatrini, ; Chou, Chen, Arun, & Young, ; Fall et al., ; Hongoh et al., ; Liu et al., ; Shinzato, Muramatsu, Matsui, & Watanabe, ; Thong‐On et al., ) but other 12 genera ( Massilia, Hydrogenophaga, Hydrogenophilus, Neisseria, Helicobacter, Thermomonas, Dokdonella, Acidiphilium, Hyphomicrobium, Paracoccus, Microvirga, and Peredibacter ) had not been reported previously for termite gut microbiota. We also found that there were eight of the 44 OTUs represented possible new taxa, as their 16S rRNA similarities to that of the currently known species were less than 97%.…”
Section: Resultssupporting
confidence: 58%
“…These 44 OTUs were assigned to 24 genera. We found that 12 of the 24 genera had been previously observed (Butera, Ferraro, Alonzo, Colazza, & Quatrini, ; Chou, Chen, Arun, & Young, ; Fall et al., ; Hongoh et al., ; Liu et al., ; Shinzato, Muramatsu, Matsui, & Watanabe, ; Thong‐On et al., ) but other 12 genera ( Massilia, Hydrogenophaga, Hydrogenophilus, Neisseria, Helicobacter, Thermomonas, Dokdonella, Acidiphilium, Hyphomicrobium, Paracoccus, Microvirga, and Peredibacter ) had not been reported previously for termite gut microbiota. We also found that there were eight of the 44 OTUs represented possible new taxa, as their 16S rRNA similarities to that of the currently known species were less than 97%.…”
Section: Resultssupporting
confidence: 58%
“…We ultimately chose T. odontotermitis as a candidate to be developed as a “Trojan Horse.” Trabulsiella odontotermitis is termite‐specific and was originally isolated and described from a subterranean termite from the family Termitidae ( Odontotermes formosanus ) (Chou et al ., ). It was also amongst one of the uricolytic bacteria isolated from the termite gut (Thong‐On et al ., ). The whole genome of T. odontotermitis has recently been sequenced which has pointed out many adaptations specific for termite gut environment (Personal communication, Dr. Panagiotis Sapountzis).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the structural similarity of UA to some explosives, we were interested in determining whether or not the strains isolated in this study were also capable of UA degradation. All isolates were screened for their ability to use UA as described previously [Thong-On et al, 2012], but were found to be negative for this activity (data not shown), indicating UA degradation does not play a role in these isolates ability to transform explosives.…”
mentioning
confidence: 96%
“…E. cloacae has been previously isolated from the termite gut and used as a shuttle organism to deliver and spread foreign genes in termite colonies [Husseneder and Grace, 2005;Zhao et al, 2008]. Interestingly, members of the genera Enterobacter, Serratia, and Lactococcus , representing uricolytic isolates, have also been isolated from the hindguts of Reticulitermes [Thong-On et al, 2012]. Uric acid (UA) degrading bacteria have been shown to play a key role in the recycling of nitrogenase waste as termites lack UA utilization activity [Potrikus and Breznak, 1981].…”
mentioning
confidence: 99%